Member of the committe - Vyrides, Ioannis (My University, 2026)
2018 - today: Member of the committee (2018,2019,2020,2021) for the Pancyprian Environmental Awards for Organizations and Businesses – EnvAwards. Annual awards. Dr Vyrides is the representative of the Cyprus University of Technology. The awards are co-organized by the Cyprus Centre for Environmental Research and Education (CYCERE) and the Office of the Commissioner for the Environment and under the auspices of the Cyprus University of Technology (CUT), the Association of Employers and Industrialists, the Cyprus Tourism Businesses Association, the Organization of Professional Women Entrepreneurs of Limassol http://kykpee.org/en/envawards/